Digital nutrition interventions and dietary adherence outcomes in Indonesia: A systematic review - Muh Siddik Ibrahim; Besse Dahlia; Juwitriani Alwi (Journal of Public Health and Development, 2026)
The growing burden of diet-related diseases in Indonesia highlights the need for innovative strategies to improve dietary behaviors. Digital nutrition interventions, including mobile applications and tele-nutrition services, have emerged as potential tools to support dietary adherence; however, evidence from the Indonesian context remains fragmented. This systematic review aimed to synthesize existing evidence on the effectiveness of digital nutrition interventions in improving dietary adherence and nutrition-related outcomes in Indonesia. A systematic review was conducted following the PRISMA 2020 guidelines. Articles published between 2015 and 2025 were retrieved from PubMed, ScienceDirect, and SpringerLink. Eligible studies included empirical research evaluating digital nutrition interventions among Indonesian populations and reporting dietary or nutrition-related behavioral outcomes. Methodological quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. Ten studies met the inclusion criteria, encompassing a total of diverse population groups, including adolescents, pregnant women, caregivers, and community health workers. The reviewed interventions included mobile-based applications, web-based platforms, tele-nutrition services, and messaging-based tools. Early evidence suggests that these interventions were associated with short-term improvements in nutrition knowledge, dietary diversity, and self-monitoring behaviors, with several studies reporting statistically significant effects compared to baseline or control conditions. However, the magnitude and consistency of outcomes varied across studies. Quality appraisal indicated that two studies were of high methodological quality, while eight were rated as having moderate quality. Overall, early evidence suggests that digital nutrition interventions may support dietary adherence and positive nutrition-related behaviors in Indonesia, particularly when combined with professional support. Further high-quality, longitudinal studies are needed to assess long-term impacts, scalability, and integration within national nutrition and primary health care systems.